Detraining in young soccer players - Melchiorri, G.; Ronconi, M.; Triossi, T.; Viero, V.; de Sanctis, D.; Tancredi, V.; Salvati, A.; Padua, E.; Alvero Cruz, J. R. (The Journal of Sports Medicine and Physical Fitness, 2014)
BACKGROUND: Two types of detraining can be described: short-term detraining with a period of less than 4 weeks, and long-term detraining (period longer than 4 weeks). The purpose of this study is to verify the presence and eventually the magnitude of physiological cardiorespiratory changes in young team sport players after a period of long-term detraining.